2007
DOI: 10.1016/j.pain.2006.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vibration perception thresholds in individuals with diffuse upper limb pain and carpal tunnel syndrome

Abstract: The study objective was to compare vibration perception and patterns of blood flow in outpatients with diffuse upper limb pain disorder (ULPD), carpal tunnel syndrome (CTS) and age and sex matched healthy controls. Vibration perception and discrimination thresholds were compared in subjects with ULPD (n=27), CTS (n=27) and healthy matched controls (n=54). Vibration measurements were taken bilaterally at three sites: (a) over the dorsum of the second and (b) fifth metacarpals and (c) the palmar aspect of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 22 publications
7
35
1
Order By: Relevance
“…Unlike stated in their letter (Tamburin and Zanette, 2011), we did observe altered vibration and cold detection thresholds over the median innervation territory of the hand. This impairment is in agreement with earlier reports by both Tucker et al (2007) and Tamburin et al (2010). The testing location of the shaft of the first metacarpal was specifically chosen to compare the results of our study with QST data that were available at the time the study was designed (Tucker et al, 2007;de la Llave-Rincon et al, 2009).…”
supporting
confidence: 88%
“…Unlike stated in their letter (Tamburin and Zanette, 2011), we did observe altered vibration and cold detection thresholds over the median innervation territory of the hand. This impairment is in agreement with earlier reports by both Tucker et al (2007) and Tamburin et al (2010). The testing location of the shaft of the first metacarpal was specifically chosen to compare the results of our study with QST data that were available at the time the study was designed (Tucker et al, 2007;de la Llave-Rincon et al, 2009).…”
supporting
confidence: 88%
“…70 Several studies have demonstrated that LE is characterized by bilateral sensory 21,22,53 and motor 6,54 changes, suggesting central sensitization mechanisms. Furthermore, vibration, 63 thermal, 19 and motor 29 impairments have been identified bilaterally in patients with unilateral CTS, which also suggests the presence of central mechanisms. A recent study demonstrated that LE is different to CTS in some sensory disturbances, as no deficit in thermal and vibration detection thresholds were found in individuals with LE.…”
Section: Participants P Atients Diagnosed With Cts Bymentioning
confidence: 85%
“…In subjects with other disorders, for example diffuse upper limb pain disorders [17], chronic whiplash [18] and different unilateral muscoskeletal disorders that encompass diffuse pain, such as frozen shoulder and epicondylitis [19], previous studies have shown decreased pain thresholds but raised detection of vibration and thermal thresholds both ipsilaterally and contralaterally to the affected limb. Such findings have suggested a common generalised disturbance of somatosensory processing and changed central nervous perception, rather than peripheral nerve dysfunction in patients with such chronic pain syndromes [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings have suggested a common generalised disturbance of somatosensory processing and changed central nervous perception, rather than peripheral nerve dysfunction in patients with such chronic pain syndromes [17,20]. In contrast to this, it has been shown that patients with fibromyalgia have hypersensitivity to pain, but normal perception thresholds [21,22], which indicates that different mechanisms are involved in the various pain syndromes.…”
Section: Discussionmentioning
confidence: 99%